Energy for sustainable society : from resources to users - Soysal, Oguz A., 1951-; Soysal, Hilkat S., 1952- (John Wiley & Sons, Inc., 2020)
"The text presents energy flow from primary sources to end-users with an interdisciplinary system approach. Technical topics include the current availability and future of primary sources, energy supply chain, conversion between different forms of energy, security of energy supply, and efficient end-use of energy sources. The sequence of the topics is organized considering the share of various sources and conversion techniques in the current global energy-supply mix. Each chapter contains a background information, an outline of the current technologies, and potential future developments. In addition to the technical content, global, economic, societal, ethical, and environmental issues associated with currently used energy technologies are discussed throughout the text. The aim of this book is to provide the readers with adequate technical foundation to evaluate the performance of energy systems and understand their interactions with socioeconomic indicators"--